HUBUNGAN KECEPATAN REAKSI DAN DAYA LEDAK OTOT TUNGKAI TERHADAP HASIL TENDANGAN SAMPING (CECHUITUI) PADA ATLET WUSHU KATEGORI SANSHOU FIK UNP - Nurtia Nilam Sari (JURNAL PENDIDIKAN ROKANIA, 2016)
This study aims to look at the relationship the reaction speed and explosive power leg muscles to kick the side of the athlete Wushu Sanshou category Nikken UNP. This study is correlational is to determine how much the relationship variables with one another. The population in this study is the athletes Wushu Sanshou category Nikken UNP totaling 20 people, and the sample amounted to 17 people were executed in the place of training athletes Wushu Sanshou categories in November 2011 by using purposive sampling technique. Based on the calculation of product moment correlation, 1) There is no significant relationship between the rate of reaction to the result side kick (cechuitui) in athletes Wushu class Sanshou Nikken UNP obtained rhitung = 0.045 <rtabel = 0.482, 2) There is a significant correlation explosive power of leg muscles the results side kick (cechuitui) at Athletes Wushu class Sanshou Nikken UNP obtained rhitung = 0.584> rtabel = 0.842, 3) There is a significant correlation reaction speed and explosive power leg muscles to kick the side (cechuitui) at Athletes Wushu Category Sanshou Nikken UNP obtained rhitung = 0.618 obtained Fhitung = 4.341> F table = 3.59